Peningkatan Derivate Product Pepaya di Desa Mayangan Kecamatan Gumukmas - Lilis Yuliati; Siti Komariyah (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Mayangan Village, Gumukmas Subdistrict, Jember Regency is an abundant village producing papaya fruit, but so far the products have only been sold in fruit form, and are not processed in derivative products, even though the papaya fruit is rotten quickly after being cooked. Therefore, efforts need to be made to increase the value added by empowering the community to be willing and collaborating to manage papaya production into products that have high economic value, as well as a means to increase people's income. The purpose of this service activity is to provide a real solution to the process of processing post-harvest papaya through the diversification of processed products made from papaya into several products whose economic value added is far higher. The results of this service are as follows: 1) produce candied papaya with various variations; 2) produce papaya dodol products; 3) help from the marketing aspect in the initial stages, namely designing the branding of the products produced under the name "Bolo Dewo"; 4) teach estimation of profits obtained from receipt of products sold with the assumption that the products sold are all sold; 5) conduct evaluation after the service program.